ChemInform Abstract: A Chiral Phosphoric Acid Catalyst for Asymmetric Construction of 1, 3‐Dioxanes. Issue 46 (November 2015) - Matsumoto, Akira; Asano, Keisuke; Matsubara, Seijiro
Abstract (E)‐5‐Hydroxy‐1‐arylpent‐2‐en‐1‐ones as well as the corresponding alkyl and alkenyl derivatives are transformed with hexanal according to the title reaction, thus furnishing 1, 3‐dioxanes in high yields and with high enantiomeric excess.